Reflexões sobre o feminino: a construção discursiva da mulher negra, na Revista Raça Brasil - Souza, Jacilene da Silva (2016)
Revista Raça Brasil is a magazine destined to the black audience and it aims to rescue the self steam of the black race, in order to rescue it, the magazine publishes in its contents, media highlights intending to show the idea that it is possible for the black people to move upward in society too. The magazine was launched in trade environment in 1996, among other magazines that did not succeed, Revista Raça Brasil is the one which is most sedimented. This master’s thesis aims to analyze discursive aspects about the black woman, in the magazine mentioned, mainly focusing on reflection about the female aspect. Based on the Discourse Analysis which seeks in speaking flaw and in the silencing possible senses and it is based on the analysis of historical and ideological constructions which constitute the utterance. It will be analyzed the discourses that move in the magazine trying to show that even a magazine which aims to value the black beauty, it utters discourses that reinforce the non-acceptance of black people as potential beings who have their own beauty. It is possible to find in the magazine discourses which ignore the black beauty as legitimate and black women represented based on European beauty standards. It is possible to query, through Revista Raça Brasil how black women discursive construction happens, being, thus relevant for the comprehension about what means being a woman as well as which positions she occupies. This research is theoretically based on French Discourse Analysis, specifically studies of Orlandi and Pêcheux (1997). Thus, some categories such as “already-said” marks about black women which constitute the interdiscourse, and ideological and discursive formations in which black women are represented in the magazine.